PENERAPAN MAQASHID SYARIAH DALAM EKONOMI ISLAM - Permata Sari, Intan; Sri Wahyuni, Eka; Hartini, Kustin (Universitas Muhammadiyah Bengkulu, 2023)
This study aims to determine the urgency of maqashid sharia in Islamic economics and to determine the application of maqashid sharia based on its business aspects. This type of research, namely library research relating to library data collection methods, uses a qualitative approach. The results of the study show that maqashid sharia has a dual role, namely: as a control tool as well as a social engineering tool to realize human benefit. It provides a rational philosophical foundation of economic activity. Without maqashid sharia, the understanding and practice of Islamic economics will become narrow, rigid, static and slow. Islamic economics will lose the spirit and substance of its shari'ah. In the application of maqashid business in the Islamic economy, it can be seen that every agreement must be clear, the obligation to work and produce, Al-Kharraj bi adh-Dhaman (Balance between Profits and Risks), maqashid prohibits gharar and maqashid prohibits wasting wealth.